Microwve and RF design of wireless systems - David M. Pozar (John Wiley & Sons, 2001)
This book presents every aspects of modern wireless system desig from the antenna to the baseband level. It offers the most complte and up-to-date presentation of the operation and design of modern wireless telecommunication systems, covering antennas and propagation, noise characterization of systems and components, digital modulation methods, and the design and operation of wireless components such as filters, amplifiers, mixers, and phase-locked loops.